2009
DOI: 10.1016/j.jaci.2009.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and immune regulation with peanut oral immunotherapy

Abstract: Background-Oral immunotherapy (OIT) has been thought to induce clinical desensitization to allergenic foods, but trials coupling the clinical response and immunologic effects of peanut OIT have not been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
633
6
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 626 publications
(693 citation statements)
references
References 39 publications
44
633
6
10
Order By: Relevance
“…Oral SIT possesses a high potential for the development of novel treatment modalities. In fact such approaches including oral immunotherapy for food allergy are under development [89][90][91][92][93].…”
Section: Clinical Usementioning
confidence: 99%
“…Oral SIT possesses a high potential for the development of novel treatment modalities. In fact such approaches including oral immunotherapy for food allergy are under development [89][90][91][92][93].…”
Section: Clinical Usementioning
confidence: 99%
“…In addition, the IgG4 antibodies to aeroallergens can produce a decrease in the processing and presenting activity of the APCs (DCs and B cells) thereby inhibiting the binding of allergen-IgE complexes to CD23 (van Neerven et al 1999;Wachholz et al 2003). In a similar way, in patients with peanut allergy the IgE-facilitated allergen binding assay has noted the possibility that these sIgG4 antibodies have a functional role in the inhibition of CD23-medited presentation by B cells to T cells (Jones et al 2009). …”
Section: Mechanisms Of Oit In Food Allergymentioning
confidence: 99%
“…Three full-text articles and three abstracts relating to a total of six studies satisfied our inclusion criteria and were therefore included in this review (see the PRISMA flow diagram in Figure 1 and Table 1). [29][30][31][32][33][34] We also found several ongoing studies that had not yet reported on any of the outcomes of interest ( Table 2).…”
Section: Resultsmentioning
confidence: 90%